Results from recent detachment experiments in alternative divertor configurations on TCV. (21st March 2017) - Theiler, C.; Lipschultz, B.; Harrison, J.; Labit, B.; Reimerdes, H.; Tsui, C.; Vijvers, W.A.J.; Boedo, J. A.; Duval, B.P.; Elmore, S.; Innocente, P.; Kruezi, U.; et al.
Abstract: Divertor detachment is explored on the TCV tokamak in alternative magnetic geometries. Starting from typical TCV single-null shapes, the poloidal flux expansion at the outer strikepoint is varied by a factor of 10 to investigate the X-divertor characteristics, and the total flux expansion is varied by 70 % to study the properties of the super-X divertor. The effect of an additional X-point near the target is investigated in X-point target divertors. Detachment of the outer target is studied in these plasmas during Ohmic density ramps and with the ion ∇ B drift away from the primary X-point. The detachment threshold, depth of detachment, and the stability of the radiation location are investigated using target measurements from the wall-embedded Langmuir probes and two-dimensional CIII line emissivity profiles across the divertor region, obtained from inverted, toroidally-integrated camera data. It is found that increasing poloidal flux expansion results in a deeper detachment for a given line-averaged density and a reduction in the radiation location sensitivity to core density, while no large effect on the detachment threshold is observed. The total flux expansion, contrary to expectations, does not show a significant influence on any detachment characteristics in these experiments. In X-point target geometries, no evidence is found for a reduced detachment threshold despite a 2–3 fold increase in connection length. A reduced radiation location sensitivity to core plasma density in the vicinity of the target X-point is suggested by the measurements.